Redefinition of Acanthosoma and taxonomic corrections to its included species (Hemiptera: Heteroptera: Acanthosomatidae) - Tsai, Jing-Fu; Rédei, Dávid (Zootaxa, 2015)
The genus level diagnostic characters of Acanthosoma Curtis, 1824, Anaxandra Stål, 1876, and Sastragala Amyot & Serville, 1843 (Hemiptera: Heteroptera: Acanthosomatidae) are discussed. The synonymy of Acanthosoma and Anaxandra proposed by Kumar (1974) is supported. Acanthosoma and Sastragala are redefined and recognized as valid genera. The identities of various species of Acanthosoma are clarified based on their type materials, their diagnostic characters are discussed and several misidentifications in previous works are corrected. The following new or reinstated combinations and new subjective synonymies are proposed: Acanthosoma haemorrhoidale haemorrhoidale (Linnaeus, 1758) = Acanthosoma proximum Dallas, 1851, syn. nov. = Acanthosoma difficile Dallas, 1851, syn. nov. = Acanthosoma dubium Dallas, 1851, syn. nov.; Acanthosoma firmatum (Walker, 1868), comb. nov. (transferred from Sastragala) = Acanthosoma giganteum Matsumura, 1913, syn. nov.; Acanthosoma murreanum (Distant, 1900), comb. nov. (transferred from Sastragala) = Acanthosoma acutangulata Liu, 1979, syn. nov. = Sastragala neoelongata Ahmad & Moizuddin, 1990, syn. nov.; Acanthosoma rufispinum (Distant, 1887), comb. nov. (transferred from Sastragala) = Sastragala minuta Ahmad & Moizuddin, 1990, syn. nov.; Acanthosoma tauriforme (Distant, 1887) = Anaxandra longispina Liu, 1987, syn. nov.; Acanthosoma hampsoni (Distant, 1900), comb. nov. (transferred from Sastragala); Acanthosoma labiduroides Jakovlev, 1880 = Acanthosoma coralliferum Horváth, 1889, syn. nov. = Acanthosoma zanthoxylum Hsiao & Liu, 1977, syn. nov.; Acanthosoma forfex Dallas, 1851 = Acanthosoma distinctum Dallas, 1851, syn. nov.; Acanthosoma rufescens Dallas, 1851, comb. restit. = Acanthosoma elongatum Dallas, 1851, syn. nov. = Anaxandra hamata Reuter, 1881, syn. nov.; Acanthosoma nigricorne Walker, 1868 = Acanthosoma nigrospina Hsiao & Liu, 1977, syn. nov.; Acanthosoma alaticorne Walker, 1868, comb. restit. = Anaxandra laticollis Hsiao & Liu, 1977, syn. nov. New combinations resulting from synonymization of Anaxandra with Acanthosoma: Acanthosoma sichuanense (Liu, 1980), comb. nov., A. montanum (Liu, 1987), comb. nov. Species transferred to Sastragala Amyot & Serville, 1843: Sastragala nigrolineata (Stål, 1876), comb. nov.; S. sigillata (Stål, 1876), comb. nov.; S. versicolor Distant, 1910, comb. restit.; S. yunnana (Hsiao & Liu, 1977), comb. nov.; to Elasmostethus Fieber, 1860: Elasmostethus singhalensis (Distant, 1902), comb. nov. Lectotypes are designated for the following species: Acanthosoma: A. difficile, A. distinctum, A. dubium, A. elongatum, A. forfex, A. proximum; Anaxandra: A. hamata, A. nigrocornuta Reuter, 1881, A. tauriformis; Sastragala: S. murreeana, S. rufispina. A neotype is designated for Anaxandra montana. New country records: Acanthosoma alaticorne and A. rufispinum: Nepal; A. forfex: Burma (Myanmar); A. labiduroides: Burma (Myanmar) and Vietnam; A. montanum: Laos and Vietnam; A. murreeanum: India, Thailand; A. nigricorne: Nepal, Burma (Myanmar) and Vietnam; A. rufescens: Pakistan, Nepal, Taiwan, Burma (Myanmar), Thailand, Laos and Vietnam.